Mitochondrial DNA heteroplasmy analysis in keratoconus patients from China - Xu, Liyan; Yang, Kaili; Fan, Qi; Gu, Yuwei; Ren, Shengwei (Frontiers in Genetics, 2023)
Background: Mitochondrial DNA (mtDNA) variants have been implicated in keratoconus (KC). The present study aimed to characterize the mtDNA heteroplasmy profile in KC and explore the association of mitochondrial heteroplasmic levels with KC. Methods: Mitochondrial sequencing of peripheral blood samples and corneal tomography were conducted in 300 KC cases and 300 matched controls. The number of heteroplasmic and homoplasmic variants was calculated across the mitochondrial genome. Spearman’s correlation was used to analyze the correlation between the number of heteroplasmic variants and age. The association of mtDNA heteroplasmic level with KC was analyzed by logistic regression analysis. Moreover, the relationship between mitochondrial heteroplasmic levels and clinical parameters was determined by linear regression analysis. Results: The distribution of mtDNA heteroplasmic variants showed the highest number of heteroplasmic variants in the noncoding region, while the COX3 gene exhibited the highest number in protein-coding genes. Comparisons of the number of heteroplasmic and homoplasmic nonsynonymous variants in protein-coding genes revealed no significant differences between KC cases and controls (all P>0.05). In addition, the number of heteroplasmic variants was positively associated with age in all subjects (r=0.085, P=0.037). The logistic regression analyses indicated that the heteroplasmic levels of m.16180_16181delAA was associated with KC (P<0.005). Linear regression analyses demonstrated that the heteroplasmic levels of m.16180_16181delAA and m.302A>C were not correlated with thinnest corneal thickness (TCT), steep keratometry (Ks), and flat keratometry (Kf) (all P>0.05) in KC cases and controls separately. Conclusion: The current study characterized the mtDNA heteroplasmy profile in KC, and revealed that the heteroplasmic levels of m.16180_16181delAA were associated with KC.